Aproximación a los intereses e inquietudes de los profesores en formación inicial de español a partir del análisis de los portafolios reflexivos en lo que se refiere a «Dar clase» - Lorenzo, Mónica (2019)
The research presented below is part of the professional Masters in language teaching (Portuguese as a mother tongue + foreign language or two foreign languages), in which the foreign language (or one of them) is Spanish, at the Faculty of Arts and Humanities of the University of Porto. This training enables future teachers to practice the teaching profession in the third cycle of basic education and secondary education in Portugal. During the second year of these postgraduate courses, teaching practice in secondary schools is envisaged; in addition, the regulation of these Master's degrees requires the trainees to prepare a portfolio related to this experience. In the area of Spanish, this document is conceived as a portfolio of reflective nature and one of its sections is based on the European Portfolio for Student Teachers of Languages (EPOSTL). To carry out this study, a total of 60 portfolios have been collected, covering the period from 2014 to 2017. Among them, descriptors have been selected for one of the seven EPOSTL categories: "Conducting a lesson"; in order to analyse the didactic aspects in which future Spanish teachers focus their concerns and interests on during their training period.